Political Communication Strategies of Muhammadiyah: Case on Medan City Mayoral Election in 2020 - Ahmad Sampurna; Hasrat Efendi Samosir; Muhammad Fitriyus; Katimin Katimin (FISIP Universitas Islam Negeri Raden Fatah Palembang, 2023)
The aim of this research was to analyze the political communication strategies employed by the leadership of Muhammadiyah in the Helvetia branch during the 2020 Medan City Election. A qualitative descriptive method was utilized, incorporating an informal selection process and triangulation of sources to ensure data accuracy. While examining Muhammadiyah's organizational structure, it becomes apparent that the union does not have a formal commitment to endorse a specific mayoral candidate. However, at the leadership level, individual roles are assumed, and personal efforts are made or instructions are given to subordinates and colleagues within the organization, as well as to trade unions. Political communication within Muhammadiyah, particularly by branch leaders in the context of the 2020 Medan City Election, is not governed by specific union regulations. Nevertheless, the leadership provides an overview to union members regarding the selection of a mayoral candidate, aiming to align organizational aspirations without causing harm to the union's interests. The Regional Head Elections, as a democratic mechanism, are founded on the principles of people's sovereignty and are implemented to strengthen Indonesian democracy. The alignment of organizational leadership, notably within Muhammadiyah, provides guidance to its union members, conveying the organization's support for a particular figure or candidate for the mayoral or regional leadership positions. Muhammadiyah's involvement in politics is part of its cultural movement, contributing to the shaping of local governance and societal development.